Intersecting sets ([New York : Distributed by Harper & Row)
Introduces inequalities, and uses them to illustrate some elementary terms in set language. Then examines the link between simple algebraic inequalities and geometric regions of a plane.
Converted into VHS 1/2 in. and DVD.
Bahan rosak (Lupus)
Keywords: Inequalities (Mathematics)